Silica Nanoparticles, Synthesis, Modification And Their Applications In The Fabrication Of Polypyrrolebased Silica Nanocomposites - Mohammad , Jafarzadeh (2010)

(untitled)
A modified preparation of silica nanoparticles via sol-gel process is described. The ability to control the particle size and distribution is found to be highly dependent on mixing modes of the reactants and drying techniques. The mixture of tetraethoxysilane (TEOS) and ethanol followed by addition of water (Mode-A) produce monodispersed powder with an average particle size of 10.6 ± 1.40 nm and a narrow size distribution. The freeze drying technique (FD) further improves the quality of the powder compared to heat drying (HD).